Proliferation and Differentiation in the Adult Subventricular Zone Are Not Affected by CSF1R Inhibition - Kyle, Jackson; Wu, Michelle; Gourzi, Stefania; Tsirka, Stella E. (Frontiers in Cellular Neuroscience, 2019)
Microglia are reported to have significant roles in regulating normal mammalian adult neurogenesis. There are two neurogenic niches in the adult mammal brain: the subgranular zone in the hippocampus, and the subventricular zone (SVZ), which makes up the lining of the lateral ventricles. While the microglia interactions on adult neurogenesis in the hippocampus have been characterized, the SVZ niche is not as well investigated. The SVZ niche is unique in that the newborn neurons migrate a much longer distance through multiple brain structures compared to newborn neurons in the hippocampus, making it more difficult to fully characterize how microglia influence this process. To examine the SVZ niche and migration pathway, we used the colony stimulating factor 1 receptor (CSF1R) antagonist PLX5622, which promotes brain wide microglia ablation. Microglia ablation resulted in no changes in the numbers of neural stem cells, transient amplifying cells, and neuroblasts. Microglia ablation in the olfactory bulb was decreased compared to the SVZ. CSF1R inhibition had no effect on the ability of microglia to proliferate. Thus, our data suggest that microglia are not required for normal functioning SVZ adult neurogenesis.